Analisis Implementasi Software Inventory DPACK-R Pada PT Indragiri Makmur Sentosa Menggunakan Metode Fungsi Borda - Heri Nuryanto (Computer Based Information System Journal, 2015)
Supply problems often faced by decision makers, especially in the areas of inventory, both in the production of goods and services. Basically a company that does the production process must perform inventory control to create a precision in planning the amount of production that will be sold to the market. If the amount of goods produced too few compared to the number of requests from consumers, it will result in loss of consumer confidence on the company so that the impact for companies which are losing the opportunity to earn profits and likely to pay much larger to meet the demand. Conversely, if the number of requests from consumers is smaller than the amount of goods produced, the company suffered losses of these conditions resulting from the increase storage costs, material waste not channeled, depreciation expense, interest embedded in inventory costs, insurance, taxes, engine failure, and decrease price. DPACK-R System is a kind of inventory management that are used by companies Indragiri Makmur Sentosa Yamaha dealer to make transactions demand for goods both in the number of parties or units. In this system other than inventory activity, there are several other activities such as: order entry, purchase, accounts receivable and payable, marketing, master, and systems.